2018
DOI: 10.18805/lr-402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage practices and fertilizer management on the growth and nitrogen efficiency in soybean

Abstract: A field experiment was performed to evaluate the effects of tillage systems and fertilizer management on the growth and nutrient uptake in soybean. The plant height, fresh weight and dry weight of conventional tillage (CT) were much higher those observed for no-tillage (NT). The highest plant height (128.47 cm) was observed in CT with chemical fertilizer. The plant nitrate concentration was higher (2.29%) in NT with green manure than chemical fertilization. However, nitrogen increased steadily in all treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Environmentally, the soils of semi-arid region suffer from degradation due to intensive tillage practices (Mrabet, 2000). Roy et al (2018) and Abolla et al (2020) reported that No-till systems effect are more beneficial in enhancing soil chemical propriety and soil fertility compared to tillage practices. It is also reported that direct crop seeding reduce about 80% of soil erosion as compared to conventional tillage (Thierfelder and Wall, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Environmentally, the soils of semi-arid region suffer from degradation due to intensive tillage practices (Mrabet, 2000). Roy et al (2018) and Abolla et al (2020) reported that No-till systems effect are more beneficial in enhancing soil chemical propriety and soil fertility compared to tillage practices. It is also reported that direct crop seeding reduce about 80% of soil erosion as compared to conventional tillage (Thierfelder and Wall, 2009).…”
Section: Introductionmentioning
confidence: 99%